Synthesis of magnetic core–shell Fe3O4@PDA@Cu-MOFs composites for enrichment of microcystin-LR by MALDI-TOF MS analysis. Issue 49 (5th August 2020) - Li, Zhijian; Gong, Congcong; Huo, Panpan; Deng, Chunhui; Pu, Shouzhi
Abstract : The synthetic route of the Fe3 O4 @PDA@Cu-MOFs microspheres and enrichment process of MC-LR. Abstract : Microcystin-LR (MC-LR) is a toxin released from cyanobacteria in eutrophicated water. MC-LR is the most abundant and the most toxic among microcystins. In this work, core–shell structured copper-based magnetic metal–organic framework (Fe3 O4 @PDA@Cu-MOFs) composites were synthesized via a solvothermal reaction and a sol–gel method. The Fe3 O4 @PDA@Cu-MOFs composites showed ultra-high surface area, strong magnetic response and outstanding hydrophilicity. The Fe3 O4 @PDA@Cu-MOFs composites combined with matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF-MS) were used to analyse the content of MC-LR in real water samples. Under the optimised conditions, our proposed method exhibited good linearity within a concentration range of 0.05–4 μg L −1 and good detection even at low limits (0.015 μg L −1 ). The method was also successfully applied to analyse traces of MC-LR with quantitative recoveries for the real water samples in the range from 98.67% to 106.15%. Furthermore, it was characterized by high sensitivity, short operation time, being environmental friendly and having the ability to analyse other pollutants in the environment.